Web Technologies and Applications : 17th Asia-Pacific Web Conference, APWeb 2015, Guangzhou, China, September 18-20, 2015, Proceedings - Cheng, Reynold; Cui, Bin.; Zhang, Zhenjie; Cai, Ruichu; Xu, Jia.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 17th Asia-Pacific Conference APWeb 2015 held in Guangzhou, China, in September 2015. The 67 full papers and presented together with 3 industrial track papers and 7 demonstration track papers were carefully reviewed and selected from 146 submissions. The papers cover a wide spectrum of Web-related data management problems, and provide a thorough view on the rapid advances of technical solutions.
On The Marriage of SPARQL and Keywords -- An Online Inference Algorithm for Labeled Latent Dirichlet Allocation -- Efficient Buffer Management for PCM-Enhanced Hybrid Memory Architecture -- Efficient Location-dependent Skyline Queries in Wireless Broadcast Environments -- Distance and Friendship: A Distance-based Model for Link Prediction in Social Networks -- Multi-Label Emotion Tagging for Online News by Supervised Topic Model -- Distinguishing Specific and Daily topics -- Matching Reviews to Object Based on 2-Stage CRF -- Discovering Restricted Regular Expressions with Interleaving -- Efficient Algorithms for Distance-based Representative Skyline Computation in 2D Space -- Trustworthy Collaborative Filtering through Downweighting Noise and Redundancy -- A Co-Ranking Framework to Select Optimal Seed Set for Influence Maximization in Heterogeneous Network -- Hashtag Sense Induction Based on Co-Occurrence Graphs -- Hybrid-LSH for Spatio-Textual Similarity Queries -- Sleep Quality Evaluation of Active Microblog Users -- Distributed XML Twig Query Processing using MapReduce -- Sentiment Word Identification with Sentiment Contextual Factors -- Large-Scale Graph Classification based on Evolutionary Computation with Map Reduce -- Multiple Attribute Aware Personalized Ranking -- Knowledge Base Completion Using Matrix Factorization -- MATAR: Keywords Enhanced Multi-Label Learning for Tag Recommendation -- Reverse Direction-based Surrounder Queries -- Learning to Hash for Recommendation with Tensor Data -- Spare Part Demand Prediction based on Context-aware Matrix Factorization -- Early Outbreak Detection in Social Networks -- Location Sensitive Friend Recommendation in Social Network -- A Compression-Based Filtering Mechanism in Content-Based Publish/Subscribe System -- Sentiment Classification for Chinese Product Reviews Based on Semantic Relevance of Phrase -- Overlapping Schema Summarization based on Multi-label Propagation -- Analysis of Subjective City Happiness Index Based on Large Scale Microblog Data -- Tree-Based Metric Learning for Distance Computation in Data Mining -- GSCS - Graph Stream Classification with Side Information -- A Supervised Parameter Estimation Method of LDA -- Learning Similarity Functions for Urban Events Detection by Mining Hotline Phone Records -- Answering Spatial Approximate Keyword Queries on Disks -- Hashing Multi-Instance Data from Bag and Instance Level -- A Multi-news Timeline Summarization Algorithm Based on Aging Theory -- Extended Strategies for Document Clustering with Word Co-occurrences -- A Lightweight Evaluation Framework for Table Layouts in MapReduce Based Query Systems -- An Extended Graph-based Label Propagation Method for Readability Assessment -- Simple is Beautiful: An Online Collaborative Filtering Recommendation Solution with Higher Accuracy -- Random-based Algorithm for Efficient Entity Matching -- A New Similarity Measure Between Semantic Trajectories based on Road Networks -- Effective Citation Recommendation by Unbiased Reference Priority Recognition -- UserGreedy: Exploiting the Activation Set to Solve Influence Maximization Problem -- AILabel: A Fast Interval Labeling Approach for Reachability Query on Very Large Graphs -- Graph-based Hybrid Recommendation Using Random Walk and Topic Modeling -- RDQS: A Relevant and Diverse Query Suggestion Generation Framework -- Minimizing the cost to win competition in social network -- Ad Dissemination Game in Ephemeral Networks -- User Generated Content Oriented Chinese Taxonomy Construction -- Mining Weighted Frequent Itemsets with the Recency Constraint -- Boosting Explicit Semantic Analysis by Clustering Paragraph Vectors of Wikipedia Articles -- Research on Semantic Disambiguation in Treebank -- PDMA: A Probabilistic Framework for Diversifying Recommendation Lists -- User Behavioral Context-Aware Service Recommendation for Personalized Mashups in Pervasive Environments -- On Coherent Indented Tree Visualization of RDF Graphs -- Online Feature Selection based on Passive-Aggressive Algorithm with Retaining Features -- Online Personalized Recommendation Based on Streaming Implicit User Feedback -- A Self-Learning Rule-based Approach for Sci-tech Compound Phrase Entity Recognition -- Batch Mode Active Learning For Geographical Image Classification -- A Multi-view Retweeting Behaviors Prediction in Social Networks -- Probabilistic Frequent Pattern Mining by PUH-Mine -- A Secure and Efficient Framework for Privacy Preserving Social Recommendation -- DistDL: A Distributed Deep Learning Service Schema with GPU Accelerating -- A Semi-Supervised Solution for Cold Start Issue on Recommender Systems -- Hybrid Cloud Deployment of an ERP-based Student Administration System -- A Benchmark Evaluation of Enterprise Cloud Infrastructure -- A Fast Data Ingestion and Indexing Scheme for Real-time Log Analytics -- A Fair Data Market System with Data Quality Evaluation and Repairing Recommendation -- HouseIn: A Housing Rental Platform with Non-Redundant Information Integrated from Multiple Sources -- ONCAPS: An Ontology-based Car Purchase Guiding System -- A Multiple Trust Paths Selection Tool in Contextual Online Social Networks -- EPEMS: An Entity Matching System For E-Commerce Products -- PPS-POI-Rec: A Privacy Preserving Social Point-of-Interest Recommender System -- Incorporating Contextual Information into a Mobile Advertisement Recommender System. .
Keywords: Data mining; Information storage and retrieva; Database management; Multimedia systems; Computer Communication Networks; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Database Management; Information Systems Applications (incl. Internet).; Multimedia Information Systems; Computer Communication Networks